Association between plasma perfluoroalkyl substances and high-grade serous ovarian cancer overall survival: A nested case-control study - Wei-Yi Xing; Fang-Hua Liu; Dong-Dong Wang; Jia-Ming Liu; Wen-Rui Zheng; Jia-Xin Liu; Lang Wu; Yue-Yang Zhao; He-Li Xu; Yi-Zi Li; Yi-Fan Wei; Dong-Hui Huang; et al. (Ecotoxicology and Environmental Safety, 2025)
Background: Although evidence suggests that perfluoroalkyl and polyfluoroalkyl substances (PFASs) are positively correlated to several disease risks, no studies have proven if plasma PFASs are related to ovarian cancer survival. Objective: To explore the association between plasma PFASs and high-grade serous ovarian cancer (HGSOC) overall survival (OS) in the population who did not smoke. Methods: We conducted a nested case-control study within the Ovarian Cancer Follow-Up Study, matching 159 dead patients and 159 survival ones based on body mass index, sample date, and age at diagnosis. Nine plasma PFASs were extracted by solid phase extraction and measured using a liquid chromatography system coupled with tandem mass spectrometry. Baseline plasma concentrations of perfluorinated carboxylic acids (PFCAs) [perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), and perfluoroheptanoic acid (PFHpA)] and perfluorinated sulfonic acids (PFSAs) [perfluorooctane sulfonic acid (PFOS) and perfluorohexane sulfonic acid (PFHxS)] were calculated. Odds ratios (ORs) and corresponding 95 % confidence intervals (CIs) were calculated via conditional logistic regression models. To elucidate the combined effects, Bayesian kernel machine (BKMR), and regression quantile g-computation (QGC) models were utilized. Result: In full-adjusted model, significant differences were observed between HGSOC survival and perfluorobutane sulfonic acid, PFHpA, PFHxS, PFOS, PFCA, and PFSA. ORs and 95 %CIs were 2.74 (1.41–5.31), 1.97 (1.03–3.76), 2.13 (1.15–3.95), 2.28 (1.16–4.47), 3.74 (1.78–7.85), and 2.56 (1.31–5.01), respectively for the highest tertile compared with the lowest tertile. The QGC and BKMR models indicated that elevated concentrations of PFAS mixtures were associated with poor OS in HGSOC. Conclusions: Both individual and mixed plasma PFASs may relate to poor OS of HGSOC. Further research is necessary to establish causality, and it is recommended to reinforce environmental risk mitigation strategies to minimize PFAS exposure.